The Axial Alignment of Titin on the Muscle Thick Filament Supports Its Role as a Molecular Ruler. Issue 17 (7th August 2020) - Bennett, Pauline; Rees, Martin; Gautel, Mathias
Abstract: The giant protein titin is expressed in vertebrate striated muscle where it spans half a sarcomere from the Z-disc to the M-band and is essential for muscle organisation, activity and health. The C-terminal portion of titin is closely associated with the thick, myosin-containing filament and exhibits a complex pattern of immunoglobulin and fibronectin domains. This pattern reflects features of the filament organisation suggesting that it acts as a molecular ruler and template, but the exact axial disposition of the molecule has not been determined. Here, we present data that allow us to precisely locate titin domains axially along the thick filament from its tip to the edge of the bare zone. We find that the domains are regularly distributed along the filament at 4-nm intervals and we can determine the domains that associate with features of the filament, such as the 11 stripes of accessory proteins. We confirm that the nine stripes ascribed to myosin binding protein-C are not related to the titin sequence previously assumed; rather, they relate to positions approximately 18 domains further towards the C terminus along titin. This disposition also allows a subgroup of titin domains comprising two or three fibronectin domains to associate with each of the 49 levels of myosin heads in each half filament. The results strongly support the role of titin as a blueprint for the thick filament and the arrangement of the myosin motor domains. Graphical abstract: Unlabelled Image Highlights: Titin domains were localised in muscle A-bands by STORM and STED microscopy. Titin A-band domains uniformly span the cross-bridge region of the thick filament. The titin domains that colocalise with accessory protein stripes are determined. The titin domain pattern matches the 49 levels of myosin in the half filament. The role of titin as a blueprint for the thick filament is strongly supported.